1996
DOI: 10.1071/rd9961137
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of immunoreactive inhibin in the plasma of mares and fetal gonads during the second half of pregnancy

Abstract: Plasma concentrations of immunoreactive (ir)-inhibin were measured in seven pregnant mares from around Day 140 of gestation to Day 2 after parturition using a heterologous bovine-based radioimmunoassay (RIA). Concentrations of luteinizing hormone (LH), follicle-stimulating hormone (FSH), oestradiol-17 beta, progesterone and relaxin were also measured in the same samples. A marked increase in plasma concentrations of ir-inhibin, FSH and LH occurred between Day 220 and Day 300 of gestation but the concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 0 publications
4
31
1
Order By: Relevance
“…The only consistent feature of previous studies of FSH concentration occurred during the last days of pregnancy when there appeared to be an increase, beginning 30 days prior to parturition [3,7,14]. This rise in ir-IGF-I and FSH levels and the timing of the first ovulation 10-14 days later corresponds to what is seen at mid-diestrus in the mare, leading to a wave of follicular growth and ovulation 10-14 days later [10,13].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The only consistent feature of previous studies of FSH concentration occurred during the last days of pregnancy when there appeared to be an increase, beginning 30 days prior to parturition [3,7,14]. This rise in ir-IGF-I and FSH levels and the timing of the first ovulation 10-14 days later corresponds to what is seen at mid-diestrus in the mare, leading to a wave of follicular growth and ovulation 10-14 days later [10,13].…”
Section: Discussionsupporting
confidence: 52%
“…Plasma IGF-I concentrations were measured by a double-antibody RIA procedure [10] as described in a previous paper [4]. Levels of immunoreactive (ir-) inhibin, follicle stimulating hormone (FSH), luteinizing hormone (LH), equine chorionic gonadotrophin (eCG), estradiol-17β (E 2 ) and progesterone (P 4 ) in peripheral blood were measured by RIA as described in previous papers [2,4].…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Recently, Nambo et al [13] reported the presence of high concentrations of immunoreactive (ir)-inhibin in the plasma of pregnant mares and demonstrated that ir-inhibin was present in the equine fetal ovary, though its homogenate showed no suppressive activity on pituitary FSH secretion. This does not, however, exclude the possibility that inhibin and/or inhibin α-subunit related molecules probably produced in equine fetal gonads might be functioning as paracrine/autocrine factors.…”
Section: Discussionmentioning
confidence: 99%
“…In equine, plasma concentrations of immunoreactive (ir) inhibin, inhibin A, inhibin pro-αC, FSH, and estradiol-17β during the estrous cycle in mares and their relationship with follicular growth have been reported [10]. Our previous studies have shown that high concentrations of ir-inhibin were present in homogenates of equine fetal ovaries at Day 190 of gestation [12]. Furthermore, immunohistochemical staining revealed the presence of inhibin α and inhibin/activin (β A and β B ) subunits in the interstitial cells of equine fetal ovaries, showing that the main sources of the large amounts of inhibins in fetal circulation are the interstitial cells of the ovary, and are not, therefore, of maternal origin [17].…”
mentioning
confidence: 99%